Bio‐Sourced Poly l‐Lactide‐Flax Composites with Close to Maximum Stiffness at Low Fiber Content through Two‐Stage Annealing. Issue 10 (6th August 2021) - Nutenki, Rajendar; Van Velthem, Pascal; Kuete, Martial; Lezaak, Matthieu; Destoop, Vincent; Ballout, Wael; Pardoen, Thomas; Bailly, Christian
Abstract: Poly l ‐Lactide (PLLA) composites with short flax fibers (from 0 to 10 wt/wt%) with close to maximum theoretical stiffness are prepared by melt‐compounding and injection‐molding followed by a two‐step isothermal crystallization protocol that fully separates the nucleation and growth stages (Tammann). The use of fast chip scanning calorimetry for thermal characterization avoids the complicating issues of crystal reorganization during the cooling and heating steps between the isothermal stages. Flax fibers are very efficient and selective nucleating agents of PLLA favoring the ordered α form. The resulting morphology exhibits trans‐crystallization on the fibers surface, predominantly at fiber defects, with a clear reduction of crystal size and a very strong fiber matrix cohesion. Efficient nucleation further leads to a large reduction of the overall crystallization time. Avrami analysis evidences a reduction of crystal growth dimensionality, consistent with both optical and scanning electron microscopy. The high modulus of the composites is unambiguously related to the strong orientation of the fibers in the tensile direction, to their high aspect ratio and to the excellent matrix‐fibers cohesion. On the other hand, the tensile strength and hardness appear isotropic within experimental uncertainty and are unfavorably influenced by the presence of the fibers and by the two‐stage annealing. Abstract : Poly l ‐lactide composites with short flax fibers are double‐annealed according to the Tamman procedure. The fibers induce trans‐crystallization of the matrix and favor the ordered form. The very strong fiber‐matrix interface, the high aspect ratio of the fibers and their alignment result in remarkable stiffness in the tensile direction, close to the theoretical maximum predicted by the Voigt model.